Basic approaches to solving the problem of formation of cognitive independence (Pedagogy of Higher and Secondary Education, 2012)
Yevtushenko N. I. Basic approaches to solving the problem of formation of cognitive independence.The article is devoted to the attempts of analyzing of the most common approaches to solving the problem of formation of teachers’ cognitive independence which are allocated based on a comparison of the cognitive objectives of the teacher, the ways to achieve it and the result.
Keywords: independent work; cognitive independence; educational-cognitive activity; self-education